The first host plant dataset of Curculionidae Scolytinae of the world: miscellaneous tribes (Part 2) - Matteo Marchioro; Laura Besana; Michele Rossini; Davide Vallotto; Enrico Ruzzier; Giacomo Ortis; Isabel Martinez-Sañudo; Massimo Faccoli (Scientific Data)
Abstract Scolytinae (Coleoptera: Curculionidae) are one of the most successful groups of invasive species. They are generally moved among continents transported within live plants, timber and wood-packaging materials. The damages caused by these insects, of economic and ecological relevance, can be caused both by the direct action of burrowing within host plant tissues and by the pathogens carried by some species. In order to prevent the introduction of new and potentially harmful species by planning effective monitoring strategies, the knowledge of recorded host plants is essential. This third contribution provides a complete list of host plants, with economic categorization, for 2,193 scolytine species, belonging to 16 tribes: Amphiscolytini, Bothrosternini, Carphodicticini, Chaetophloeini, Crypturgini, Diamerini, Dryocoetini, Hexacolini, Hylesinini, Hyorrhynchini, Hypoborini, Micracidini, Phloeotribini, Phrixosomatini, Scolytini, and Scolytoplatypodini.